PERKEMBANGAN MOTORIK HALUS ANAK MELALUI KEGIATAN MENGGUNTING DAN MENEMPEL DENGAN KERTAS QUILLING SESUAI POLA GAMBAR DI TK TABITHA 1 BENTENG KELURAHAN BENTENG KOTA AMBON - Sintika Elisabeth Jalmav; H. Abarua; L. J. Lokollo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to determine the development of children's fine motor skills through cutting and pasting activities using quilling paper according to picture patterns at Tabitha 1 Kindergarten, Benteng Village, Ambon City. The study employed Classroom Action Research (CAR) with quantitative descriptive data analysis across two cycles consisting of planning, implementation, observation, and reflection phases. The research involved 13 children (7 boys and 6 girls) aged 5-6 years in group B during the 2025/2026 academic year. Fine motor skills are crucial activities for training eye-hand coordination and writing fluency, enabling children to write smoothly during their growth phase. Results from the first cycle showed one child had not yet developed adequate fine motor skills, prompting implementation of the second cycle. The second cycle assessment revealed 0% in the BB (Not Developed) category, indicating the child began developing these skills. The findings demonstrate significant improvement from cycle I to cycle II, confirming that cutting and pasting activities with quilling paper according to picture patterns effectively develop children's fine motor skills at Tabitha 1 Kindergarten, Benteng Village, Ambon City during the 2025/2026 academic year.